Edukasi Kesehatan sebagai Upaya Peningkatan Sikap Anak tentang Konsumsi Makanan dengan Gizi Seimbang: Health Education as an Effort to Improve Children’s Attitudes about Consuming Food with Balanced Nutrition - Rizona, Firnaliza; Appulembang, Yeni Anna; Rahmawati, Fuji; Aprilia, Zesi; Citra, Viona Fracellia; Padiana, Rijal Akbar Difa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Nowadays, many schoolchildren suffer from nutritional problems such as obesity, stunting, and wasting. One of the causes is the lack of understanding and attitude of children in determining food consumption with balanced nutrition. In addition to parents taking care of their children’s nutrition, children themselves also need to have the right attitude about what food is good for them. The target of this activity is elementary school children as many as 30 students to improve children’s attitudes about food with balanced nutrition through health education conducted through lectures using leaflets and monopoly educational games. The results of this activity are an increase in the attitude of elementary school students about food with balanced nutrition, namely with an attitude in the good category before education by 40% increasing to 83.33% with a good category attitude. Based on this community service activity, it is hoped that children will be more appropriate in choosing foods with balanced nutrition so that it is hoped that nutritional problems in children can be reduced.